(1030) Socialist Finance.(Basic Problems of the Theory and Practice of Finance in Poland) المالية الاشتراكية(المشاكل الأساسية لنظرية وممارسة المالية في بولندا) - Ahmed Abdel Aziz El-Sharkawi (INP, 2024)
The study explores socialist finance through a comprehensive overview detailing its purpose and scope, alongside defining basic concepts. It examines the distinctive characteristics of finance in a socialist economy, including its objective, comprehensive, uniform, and planned nature, as well as its dual-planned division. The study highlights the role of finance in the socialist economy, focusing on its primary functions: the distributive function and the control function. A list of references is provided to support the analysis.